Partial reform of the Swiss Criminal Code (Federal Statute of March 18, 1971) - Hurtado Pozo, José (1972)
This paper begins by developing the importance of understanding the modifications of the Swiss Penal Code in order to take advantage of the comparative method with respect to the elaboration and interpretation of our criminal laws. In this line, the text introduces us to the thought of Carl Stoos, who elaborated the first draft of the Swiss Criminal Code, prior to the analysis of the reform and the changes in the provisions of the Criminal Code. In this way, the author highlights the influence of Stoos' thinking, especially his postulates regarding the resocialization of the offender and also presents criticisms of the new formulations introduced in the reform regarding the approach to criminal law.